Exploring the Relationship between Economic Growth, Renewable Energy and Carbon Emissions: A Case of Cuba - Kayani, Farrukh Nawaz (International Journal of Energy Economics and Policy, 2025)
In the modern era, balancing economic growth and environmental sustainability has become one of the greatest challenges, especially for the emerging nations. As a case of examining the decoupling of economic growth from carbon emissions, Cuba’s historical reliance on fossil fuels, especially during the U.S. embargo, is quite interesting. In this article we have examined the impact of economic growth upon the carbon emissions of Cuba. We extracted annual time series data for the dependent variable (Carbon Emissions) and explanatory variables (Economic Growth and Renewable Energy Consumption) for the period spanning from 1990 to 2020. To determine the long run relationship between the variables, we used Auto regressive distributed lags (ARDL) bounds test of co-integration. The empirical findings revealed the existence of a long-run relationship among the variables of the model. We found that economic growth has a significant positive impact upon carbon emissions; furthermore, there is also a bi-directional causality between the economic growth and the carbon emissions. This research could help the policymakers to establish novel and efficient policies to tackle the environmental issues and move closer to the attainment of sustainable development goals.